A rare case report on cauda equina syndrome - Sreeram, Sai Charitha; Sampurna, Talari; Lakshmi, P. (International Journal of Basic & Clinical Pharmacology, 2017)
Cauda Equina Syndrome (CES) is a rare but serious neurologic condition in which neurological dysfunction affects the lumbar and sacral nerve roots within the vertebral canal. CES is a clinical entity consisting of low back ache, bilateral leg pain with motor and sensory deficits, genitourinary dysfunction, saddle anaesthesia and faecal incontinence. It is a rare condition with a prevalence in the general population estimated between 1:100000 and 1:33000. The presentation of CES may vary, especially in the early stages of compression. Magnetic Resonance Imaging (MRI) is the accepted gold standard modality of choice for diagnosing CES which identifies potential mimics such as aortic dissection or spinal infarction. Here we discuss a rare and unique case of CES with atypical presentation, knowledge of which is essential for early diagnosis, treatment and prevention of permanent neurological dysfunction.